1982
DOI: 10.1111/j.1440-1681.1982.tb00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylaplysinopsin: A Natural Product of Marine Origin With Effects on Serotonergic Neurotransmission

Abstract: 1. Methylaplysinopsin is an indolyl-methylene derivative of creatinin which was isolated from a sponge collected on the Great Barrier Reef. 2. It is a potent inhibitor of tetrabenazine-induced responses in rats and mice and appears to act through several mechanisms, each of which enhances central serotonergic function. 3. As a reversible inhibitor of type A monoamine oxidase (MAO) methylaplysinopsin is relatively short-acting and has a Ki of 0.2 mumol/l when serotonin is the substrate used. 4. Methylaplysinops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Methylaplysinopsin ( 1 ) (Fig. 2) isolated from Aplysinopsis reticulata by Baird-Lambert et al was reported to inhibit monoamine oxidase (MAO) and to displace serotonin from its receptors 16. Other molecules from this group: 6-bromo-2′-de- N -methylaplysinopsin ( 2 ), 6-bromoaplysinopsin ( 3 ), and N -3′-ethylaplysinopsin ( 4 ) (Fig.…”
Section: Natural Indole Alkaloids Of Marine Originmentioning
confidence: 99%
“…Methylaplysinopsin ( 1 ) (Fig. 2) isolated from Aplysinopsis reticulata by Baird-Lambert et al was reported to inhibit monoamine oxidase (MAO) and to displace serotonin from its receptors 16. Other molecules from this group: 6-bromo-2′-de- N -methylaplysinopsin ( 2 ), 6-bromoaplysinopsin ( 3 ), and N -3′-ethylaplysinopsin ( 4 ) (Fig.…”
Section: Natural Indole Alkaloids Of Marine Originmentioning
confidence: 99%
“…This activity was evaluated in tetrabenazine-induced ptosis in mice and rats. A pretreatment with methylaplysinopsin caused significant reduction in ptosis occurring in tetrabenazine treated rodents with ED 50 5 mg/kg [9,30]. Reversal of tetrabenazine ptosis has been also tested for other aplysinopsins [9].…”
Section: Biological Activitymentioning
confidence: 99%
“…An inhibition of monoamine oxidase (MAO), as well as an inhibition of the neuronal uptake of the neurotransmitters serotonin or noradrenalin, are common mechanisms accounting for the antidepressant effect [30]. In in vitro studies on mouse brain homogenate as a source of MAO, methylaplysinopsin exhibited enzyme inhibition over a wide concentration range (0.1–100 μM), especially with serotonin as a substrate.…”
Section: Biological Activitymentioning
confidence: 99%
See 2 more Smart Citations